STEM-based PjBL Learning Model with Manggaraians Indigenous Science Content to Improve Science Literacy: is it Effective? - Yuliana Wahyu; Ambros Leonangung Edu; Arnoldus Helmon (Postgraduate, University of Mataram, 2023)
This study aims to develop the effectiveness of the STEM-based PjBL (Project-Based Learning) model which incorporates Manggarai indigenous knowledge content to increase scientific literacy in elementary school students. The target population of this study were elementary school students in Langke Rembong District, Manggarai Regency. The research follows the Borg & Gall model for research and development. Data collection included administering scientific literacy tests to assess students' knowledge, attitudes, and competencies related to original science content. To assess the effectiveness of the STEM-based PjBL model, an ANOVA test was used to compare the literacy level of science students who took innovative models with students who took conventional learning. The results of hypothesis testing show that the STEM-based PjBL model has proven effective in increasing scientific literacy in various dimensions, including students' content knowledge, contextual understanding, attitudes towards science, and competency in applying scientific concepts. Notably, after implementing the product trials, significant differences in scientific literacy were observed between students who were exposed to STEM-based PjBL-based models and those who followed conventional teaching methods. These findings underscore the potential of the STEM-based PjBL approach, combined with native Manggarai science content, as an effective means of increasing science literacy among elementary school students.